2022
DOI: 10.1111/ldrp.12286
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Interventions for English Learners with Word Reading Difficulties: A Research Synthesis

Abstract: This study meta-analyzed the last four decades of reading intervention research focused on improving reading outcomes for English language (EL) students in Grades K-5 with or at risk for word reading difficulties. Experimental and quasi-experimental group design and single-case experimental design (SCED) studies were included; 10 group design and 7 SCED studies met inclusion criteria (m = 61; total student N = 2,270). Visual inspection of the effect size distribution revealed that the assumption of between-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
(350 reference statements)
0
1
0
Order By: Relevance
“…Our study also has implications for closing the EL reading achievement gap (US Department of Education, 2012) because our results suggest that it is possible to equitably screen EL and non‐EL students in first grade. Screening can allow for evidence‐based reading interventions for EL students at risk of experiencing reading challenge (see Solari et al., 2022), which could target this achievement gap. This chasm could be the result, in part, of decisions in earlier grades not to provide intensive reading intervention to EL students, even when they are at risk of experiencing reading challenge (separate from their proficiency in English; Samson & Lesaux, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also has implications for closing the EL reading achievement gap (US Department of Education, 2012) because our results suggest that it is possible to equitably screen EL and non‐EL students in first grade. Screening can allow for evidence‐based reading interventions for EL students at risk of experiencing reading challenge (see Solari et al., 2022), which could target this achievement gap. This chasm could be the result, in part, of decisions in earlier grades not to provide intensive reading intervention to EL students, even when they are at risk of experiencing reading challenge (separate from their proficiency in English; Samson & Lesaux, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The program could benefit from doubling each session, meaning assigning two sessions for students to engage with each text. This adjustment would facilitate the incorporation of repeated reading of the same text and broaden exposure to unfamiliar texts simultaneously [9,10,18], which would probably foster the efficacy of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the specific strategies implemented, we found that the multicomponent intervention, which incorporates non-repetitive reading, systematic procedures to tackling challenging words, corrective feedback, praise, exposure to different genres of texts, and opportunities for self-and hetero-assessment, were highly beneficial. These evidence-based tools, when systematically integrated into the intervention routine, significantly enhanced the reading performance of third-grade at-risk readers [9,10,18,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations